Health Tourism: Entrepreneurial Strategy of Nursing and Medical Sciences - Amanmohammad Amanjan; Parviz Saeidi; Fereidoun Azma; Majid Nasiri (Golestan University of Medical Sciences, 2022)
Abstract Background: Entrepreneurship has important role in development and expansion of health tourism. The purpose of this study was to explore the experience of faculty members on entrepreneurships in health tourism. Methods: This qualitative study was performed using the foundation data approach. Participants were selected via purposive sampling. Nineteen faculty members at Golestan University of Medical Sciences were interviewed in 2020. The individual and semi-structured interviews were conducted and continued until data saturation was achieved. The data was analyzed based on the foundation data approach. Results: Based on the results, 554 primary codes, 56 sub-categories and nine main categories were obtained. The main categories included tourism laws and standards, health tourism beneficiaries, development of entrepreneurial strategies, facilitation of health tourism infrastructure, quality of health tourism services, Iran's tourist attractions, gaining competitive advantage, technology and modern knowledge, and entrepreneurial management. Conclusion: Based on the results, having an entrepreneurial approach in the field of health tourism can turn nursing and medical sciences capacities in the Golestan Province into prosperity.